1990
DOI: 10.1590/s0036-46651990000300010
|View full text |Cite
|
Sign up to set email alerts
|

Visceral larva migrans: a seroepidemiological survey in five municipalities of São Paulo State, Brazil

Abstract: An enzyme-linked immunosorbent assay (ELISA), employing antigens from Toxocara canis larvae and the absortion of suspected sera with Ascaris lumbricoides extracts was used in a seroepidemiological study performed in five municipalities of São Paulo State, Brazil (São Paulo, Campinas, Santos, Marília and Presidente Prudente) in order to determine the frequency of antibodies to Toxocara. In 2,025 blood samples collected, 806 proceeded from male subjects and 1,219 from females; 483 samples were collected from sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
1
7

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 15 publications
5
34
1
7
Order By: Relevance
“…*Some subjects had more than one sign/symptom; **p < 0.05 = significant value (Chi-square); *** variables in the model: sex, age, pulmonary and hepatic manifestations, headache, and weakness and/or fatigue. In agreement with other authors, we have also found statistically significant differences between gender and positive serology indicating that male subjects are more associated at risk of toxocariasis than female subjects, probably because of their close contact with soil, as is the case with this population, who are farmers 4,5,21,22,26 .…”
Section: Discussionsupporting
confidence: 93%
“…*Some subjects had more than one sign/symptom; **p < 0.05 = significant value (Chi-square); *** variables in the model: sex, age, pulmonary and hepatic manifestations, headache, and weakness and/or fatigue. In agreement with other authors, we have also found statistically significant differences between gender and positive serology indicating that male subjects are more associated at risk of toxocariasis than female subjects, probably because of their close contact with soil, as is the case with this population, who are farmers 4,5,21,22,26 .…”
Section: Discussionsupporting
confidence: 93%
“…The population studied here was from an urban area with a high demographic density, a fact favoring the existence of a significant number of individuals with anti-Toxocara antibodies as well as a closer man-dog contact and high exposure to dog feces-contaminated environments (Chieffi et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The criterion adopted for the diagnosis of Toxocara infection was a serology (ELISA) titer ≥ 1/160 (Chieffi et al 1990).…”
Section: Methodsmentioning
confidence: 99%
“…A goat antihuman IgG (Gamma-Chain) specific peroxidase conjugate was used. Absorbance was read at 492 nm to establish optical density; sera with titers higher than or approximating 1:160 were considered positive 11 .…”
Section: Methodsmentioning
confidence: 99%